Development of a Fertility Restorer for inap CMS (Isatis indigotica) Brassica napus Through Genetic Introgression of One Alien Addition - Li, Pengfei; Kang, Lei; Wang, Aifan; Cui, Cheng; Jiang, Liangcai; Guo, Shizhen; Ge, Xianhong; Li, Zaiyun (Frontiers in Plant Science, 2019)
Novel Brassica napus cytoplasmic male sterility (CMS) with carpelloid stamens (inap CMS) was produced by intertribal somatic hybridization with Isatis indigotica (Chinese woad), but its RF (restorer of fertility) gene(s) existed in one particular woad chromosome that was carried by one fertile monosomic alien addition line (MAAL) of rapeseed. Herein, the selfed progenies of this MAAL were extensively selected and analyzed to screen the rapeseed-type plants (2n=38) with good male fertility and to produce their doubled haploid (DH) lines by microspore culture. From the investigation of fertility restoration in the F1 hybrids with inap CMS, one DH line (RF 39) was identified to adequately restore male fertility and likely carried one dominant RF gene. Specifically, this restorer produced brown pollen grains similar to the woad and the MAAL, suggesting that this trait is closely linked with the RF gene(s) and serves as one phenotypic marker for the restorer. This restorer contained 38 chromosomes of rapeseed and no intact chromosomes of woad, but some DNA fragments of woad origin were detected at low frequency. This restorer was much improved for pollen and seed fertility and for low glucosinolate content. The successful breeding of the restorer for inap CMS rendered this new pollination control system feasible for rapeseed hybrid production.